Pain as a Secondary Quality: A Phenomenological Approach - Escudero-Morales, Alejandro (Problemos, 2023)
This work proposes that pain meets the requirements of being characterized as a secondary quality, as it covers, like a color, a determined extension. The argument seeks to establish a literal pain-color analogy through an inquiry into the intensity and location of the pain. From the classic intensity/location relationship reported by patients with acute appendicitis, three degrees of pain are distinguished: mild, moderate, and severe. The objective is only achieved by examining the Body’s extensional determinations (primary quality) insofar as each of these degrees of pain covers three particular measures. Once these three measures have been explored according to the perforation process (tissue damage), the work ends by identifying pain as a transcendent moment.
Keywords: Pain; Husserl; intensity; secondary quality; localization